SPECTROSCOPIC-FACTOR DISCREPANCIES IN (BE-9,B-10) FOR DIFFERENT EJECTILE EXCITATIONS - Winfield, J; Jelley, N; Rae, W; Woods, C (1985)
Angular distributions have been measured for the (9Be, 10B[3+, 0.0]) and (9Be, 10B[1+, 0.72]) reactions on 63Cu, 54Fe, 26, 24Mg and 16O at 43 MeV and on 40Ca at 45 and 30 MeV. EFR-DWBA calculations which used optical potentials obtained from the measured elastic scattering of 9Be from 26Mg, 16O and 40Ca and 10B from 25Mg and 39K have generally reproduced well the shape of the cross sections. Initially, a standard prescription was used in the form-factor calculation and Cohen and Kurath spectroscopic factors were assumed for 9Be-10B. Inconsistencies, concerning whether 10B was left in its ground or first excited state, of up to 60% were found between the extracted target spectroscopic factors. This anomaly was insensitive to changes in either optical-potential or bound-state parameters. A simple calculation of a two-step process could not account for the anomaly. Use of modified spectroscopic factors for the 9Be-10B system essentially removed the discrepancies except for the magnesium targets, and an improved form-factor description further alleviated the anomaly. This form-factor method uses a shell-model potential in conjunction with a surface-peaked potential, the depth of which is adjusted to give the correct asymptotic form to the wave function. © 1985.